2020
DOI: 10.1177/0194599820912739
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Steroids on Survival of Mouse and Human Tympanic Membrane Fibroblasts

Abstract: Objective Tympanic membrane (TM) fibroblast cytotoxicity of quinolone ear drops is enhanced by dexamethasone and fluocinolone. Hydrocortisone has not been evaluated. We aimed to assess the effects of these 3 steroids on mouse and human TM fibroblast survival. Study Design In vitro. Setting Academic laboratory. Subjects and Methods Mouse and human TM fibroblasts were exposed to hydrocortisone, dexamethasone, or fluocinolone at concentrations in commercial ear drops (1%, 0.1%, or 0.025%, respectively) and at ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In this study, polypeptoid solutions were prepared at various concentrations (0.125, 0.25, 0.5, 1, and 2 mg/mL) in a complete culture medium ( Figure 8 ). Generally speaking, a sample is considered non-toxic to cells (with no cytotoxicity) when the relative cell viability is above 75% [ 38 ]. All the polypeptoid samples prepared in this study demonstrated relative cell viability above 75% for concentrations up to 2 mg/mL, indicating their non-toxicity towards cells.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, polypeptoid solutions were prepared at various concentrations (0.125, 0.25, 0.5, 1, and 2 mg/mL) in a complete culture medium ( Figure 8 ). Generally speaking, a sample is considered non-toxic to cells (with no cytotoxicity) when the relative cell viability is above 75% [ 38 ]. All the polypeptoid samples prepared in this study demonstrated relative cell viability above 75% for concentrations up to 2 mg/mL, indicating their non-toxicity towards cells.…”
Section: Resultsmentioning
confidence: 99%
“…As quinolone ear drops have only recently been shown to impact TM integrity (16)(17)(18)(19), we paid particular attention to the impact of the ear drops administered postoperatively. Corticosteroids have been known to have an inhibitory effect on TM healing for 30 years (27,28) The mechanisms responsible for the adverse effects of quinolones and steroids are complex and not fully understood (29)(30)(31)(32). However, we routinely initiate the use of these agents on the first postoperative day and continue these for a month, thereby exposing the canal and TM to relatively high concentrations during the early phase of healing.…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, an experimental study using a rat model concluded that ciprofloxacin-dexamethasone delayed healing of tympanic membrane perforations (4). A more recent paper has demonstrated that steroid preparations in commercial ear drops reduce survival of human tympanic membrane fibroblasts (5).…”
Section: Introductionmentioning
confidence: 99%